Analysis of Mind Patterns and Work Culture in Government of West Pasaman District - Sri Andri Yani; Etika Khairina; Suswanta Suswanta; Mochammad Iqbal Fadhlurrohman (Journal of Government and Civil Society, 2021)
This article Aim to analyze bureaucratic reform in the West Pasaman district government, which is related to the last stage of the 2020-2025 bureaucratic reform grand design. This projection is an opportunity to demonstrate the dedication of the bureaucracy to good governance. On the other hand, there is one thing that cannot be denied, such as the fact that the government still leaves a lot of work that has not been completed according to the target and public services that are not yet community-oriented. The performance of the West Pasaman district government’s bureaucracy is still considered low. This study uses a descriptive research method that is supported by a literature study approach by tracing the actual data for this research material. The results of this study discuss two aspects of bureaucratic reform, namely reform of mindset and work culture. Improving the mindset is used to improve the performance of the bureaucracy in order to think in a visionary direction to create a productive, innovative, and competitive bureaucracy, for this reason, the mindset is adapted from the concept of dynamic governance (Thinking ahead, Thinking Again, Thinking Across. While the work culture is aimed at creating bureaucracy agile and fast, considering the West Pasaman bureaucracy consists of two ethnicities (Mandahiling, Minang) so that it affects the work culture of each. Artikel ini bertujuan untuk menganalisis reformasi birokrasi di pemerintahan Kabupaten Pasaman Barat terkait tahapan terakhir grand design reformasi birokrasi 2020-2025. Proyek ini merupakan peluang untuk menunjukkan dedikasi birokrasi terhadap tata kelola pemerintahan yang baik. Di sisi lain, ada satu hal yang tidak bisa dipungkiri, seperti masih banyaknya pekerjaan yang belum diselesaikan pemerintah sesuai target dan pelayanan publik yang belum berorientasi pada masyarakat. Kinerja birokrasi Pemerintah Kabupaten Pasaman Barat dinilai masih rendah. Penelitian ini menggunakan metode penelitian deskriptif yang didukung dengan pendekatan studi pustaka dengan menelusuri data aktual untuk bahan penelitian. Hasil penelitian ini membahas dua aspek reformasi birokrasi, yaitu reformasi pola pikir dan budaya kerja. Perbaikan pola pikir digunakan untuk meningkatkan kinerja birokrasi agar berpikir secara visioner untuk mewujudkan birokrasi yang produktif, inovatif, dan berdaya saing. Pola pikir tersebut diadaptasi dari konsep tata kelola yang dinamis (berpikir ke depan, berpikir ulang, berpikir melintas). Adapun budaya kerja ditujukan untuk menciptakan birokrasi yang gesit dan cepat, mengingat birokrasi Pasaman Barat terdiri dari dua suku (Mandahiling, Minang) sehingga memengaruhi budaya kerja masing-masing